Are Tree Tenure and Land Tenure Issues the Same? A Case Study of Rights to Trees among the Tsamako of Southwest Ethiopia - Melesse Getu (Ethiopian Journal of the Social Sciences and Humanities, 2007)
There has been confusion as to whether land tenure and tree tenure issues should be looked at as two distinct entities or not. In this article I describe the various means of establishing rights of access to trees and other savannah woodland resources and how such rights are socially sanctioned as distinct from the overlapping land tenure system prevailing in the country today. The discussion focuses on issues raised by differential rights of access by multiple users for multiple purposes, and attempts to show the various ways of establishing tree primary user rights as distinct from those held in jointly managed woodlands. This happens, interestingly, contrary to the received wisdom that pastoralist societies ‘lack’ basic social norms let alone to have a set of rules designed to regulate the use and protection of trees. Finally, through an examination of the ways in which rules which apply to trees are enforced, both generally and in particular cases, I argue that it is the relatively low demographic density, a relatively homogeneous community and the resultant quick acquisition and dissemination of information and an inclusive decision-making system at the grass-root level which have made rule enforcement relatively easy and cost-effective. These resulted in a system which encourages tree protection and long-term oriented multiple uses. This article is based on data drawn from eighteen months of ethnographic field research which provided the author with the opportunity to employ a range of data collection techniques including key informant interviews, focus group discussions and participant observation.